(untitled) (Western European Journal of Linguistics and Education, 2024)
The use of authentic materials in EFL has long been acknowledged to be advantageous to leaners as they provide real-life experience in the language classroom. However, many of the existing definitions which most teachers are utilizing to select appropriate teaching resources present a strong bias toward the notion of “native speakers’ production”. This article aims to call for reconsideration of defining “authentic materials” by pointing out that the English language no longer belongs to the so-called “native speakers”, stating the fact that a growing number of non-native speakers are using it to communicate purposefully every day. Also, authentic materials can be ideally used in secondary schools, both to ensure real communication between users of the English language and to improve written competence in English.